(untitled) (African Journal of Biomedical Research, 2021)
Leukemia is the most common cancer in children, accounting for a prominent percentage of cancer-related death in that age-group. It is therefore very important to prevent and treat this cancer. In this study, the anticancer effects of 6 different parts of 4 selected species of medicinal plants in Nigerian, especially those grown in South-Western and South-Eastern regions, were investigated on Human leukemic-HL-60 cell line to identify potential natural alternatives for the development of antileukemic drugs and possible in vitro antioxidant activity. The plants / seeds were gathered from selected regions in Nigeria and their aerial parts extracted through repeated maceration in methanol 70%. The cytotoxic activity of extracts on human leukemic- HL-60 cell line was evaluated by Cell Counting Kit (CCK-8) assay 48 hours after treatment. The in vitro antioxidant activity was evaluated using DPPH radical scavenging method. Polyalthia longifolia seeds and leaves had marked anti-proliferative activity against HL-60 cells showing from the inhibitory concentration at 50% (IC50: 52.1 and 56.69 µg/ml respectively). In a time-dependent fashion, Polyalthia longifolia Stem bark showed the lowest DPPH radical survival rate, demonstrating its promising antioxidant status. Our findings show that, Polyalthia longifolia seed possess both growth inhibitory potential against leukemic cell lines and in vitro antioxidant activity, therefore a good candidate for further investigation for active chemopreventive or/and therapeutic principles. Also, a further exploration via mechanistic studies for possible mechanism of cytotoxicity against leukemic and other cell lines is recommended